Network change in the ipsilesional cerebellum is correlated with motor recovery following unilateral pontine infarction. (17th May 2019) - Liu, G.; Tan, S.; Peng, K.; Dang, C.; Xing, S.; Xie, C.; Zeng, J.
Abstract : Background and purpose: Patients with acute pontine infarcts generally have good short‐term motor outcomes; however, the mechanisms underlying this recovery of function remain unclear. Methods: Twenty well‐recovered patients with acute pontine infarcts and 20 well‐recovered patients with acute striato‐capsular infarcts were recruited. Fugl‐Meyer assessment and resting‐state functional magnetic resonance imaging were performed 1, 4 and 12 weeks after onset. Patients were further assigned to better and worse recovery subgroups according to the degree of motor recovery at the twelfth week after stroke. Voxel‐wise degree centrality (DC)–behavior correlation analysis was used to identify brain regions related to changes in motor function within 12 weeks after stroke. Results: A significant correlation was found between DC and Fugl‐Meyer scores within 12 weeks in the ipsilesional cerebellar crus I and crus II in patients with pontine infarction and in the ipsilesional middle temporal gyrus in patients with striato‐capsular infarction (all P  <   0.001, AlphaSim corrected). The mean DC in these areas was higher both in the better and worse recovery subgroups at the fourth than at the first week (all P  <   0.05). In addition, the mean DC values in these areas were higher in patients with better recovery at the twelfth than at the first week ( P  <   0.05), but such change was not found in patients with worse recovery. Conclusions: These results indicate that network changes in the ipsilesional cerebellum are correlated with motor recovery following pontine infarction. Motor recovery mechanisms may vary between pontine and striato‐capsular infarcts, according to lesion location.